A Review of Research on Ethical Decision-Making of Purchasing Professionals - Ho, Yi-Hui (Information Management and Business Review, 2012)
Purchasing professionals play a critical role in supporting the purchasing function. In addition to develop and maintain relationships with suppliers, they often serve as the communicator and negotiator to the external business community. It is essential to understand ethical decision-making of purchasing professionals for those who want to build reciprocal buyer-supplier relationships. This article aims to understand the trends and research opportunities of ethical decision-making of purchasing professionals based on a review of related literature. Some suggestions for future research are discussed.